Determination of structural changes efficiency in the economic system of the region in the context of implementation the Concept of Sustainable Development - Solokha, Dmytro; Bieliakova, Oksana (<center>Conference Proceedings Determinants Of Regional Development</center>; No 2 (2021): Conference Proceedings - VIII International Scientific Conference Determinants of Regional DevelopmentDO - 10.14595/CP/02/022, 2021)
The paper presents the results of scientific research to address the issue of assessing the effectiveness of structural changes in the regional economic system that take place in the context of the practical implementation of the basic principles of the Concept of Sustainable Development in Ukraine. Based on the analysis of literature sources on the profile of the research, the proposed use of the program method for the formation of strategic plans for regional development on the basis of effective functioning of system-forming both in relation to the regional economic system and for the national economy as a whole. And long-term development programs and the main tasks of such development are defined. It is proposed to introduce a system of constant monitoring of certain components of the principles of sustainable development of the regions of Ukraine, scientific circulation is recommended to be supplemented by the economic category of the effectiveness of structural changes, its characteristics are given. To assess the effectiveness of structural changes at the regional level, taking into account the requirements of sustainable long-term development, it is proposed to use an index assessment method, in particular, an aggregate index of development efficiency.